Greater than the sum of its parts: Aggregate vs aggregated inflation expectations - Alexander M. Dietrich; Edward S. Knotek; Kristian Ove R. Myrseth; Robert W. Rich; Raphael Schoenle; Michael Weber (Danmarks Nationalbank, 2024)
This paper introduces a novel measure of consumer inflation expectations: We elicit and combine inflation forecasts across categories of personal consumption expenditure to form an aggregated measure of inflation expectations. Drawing on answers from nearly 60,000 respondents, our data cover the early lowinflation environment of the covid-19 pandemic and the 2021 inflation surge. Conventionally elicited inflation expectations consistently exceed aggregated measures constructed under plausible weighting schemes. Aggregated measures display less disagreement and volatility and are stronger predictors of consumers' spending plans. The relative informational value of aggregated measures rises with the individual-level gap between conventional and aggregated inflation expectations. Our results chart a new course for designing measures of inflation expectations.
Keywords: C83; E31; E52; 330; Household expectations; Survey; Sectoral expectations; Inflation expectations